Language and Madrasa in India, Uttar Pradesh. - Arina Rohmatika (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2019)
Data India shows thatÂ Muslim population in India, at the census 2001, was in second place after Hindus. It reached 138 million (13.4%) after Hindus which is little over 827 million (80.5%). This number implies how Islam has been well-received in India and entered into various areas of life including education. Muslim Educational System in India has developed over decades through its Islamic institution and madrasas. This study aims to see the language teaching in Darul Uloom, Deoband as it is reflected through its educational system and curriculum. This is a library based research in which extensive reviews of literature has been made in attempt to produce a descriptive qualitative analysis. This study shows that in Darul Uloom Deoband, stylized writing mastery has become the ultimate skills to acquire.here,Â Language is not only merely targeted as a means of communication but also as a means to study Islamic textbooks. Moreover, it is expected that through the language mastery its students and alumni can be author of many books in Arabic and English. Language is learned comprehensively started from grammar, syntax, to Literature.Â Keywords: Language, Madrasa, Darul Uloom Deoband